IMPLEMENTASI HUMAN SECURITY DALAM KEBIJAKAN KEPENDUDUKAN INDONESIA: PERSPEKTIF MANAJEMEN POPULASI TERHADAP KETAHANAN EKONOMI, SOSIAL, DAN BUDAYA - Vieraninditha Adinda Nailla (At-Tanwir Law Review, 2026)
Indonesia, as the fourth most populous country in the world, faces complex challenges in managing population dynamics that directly impact national stability. This study analyzes the implementation of human security in Indonesia's population policy from a population management perspective on economic, social, and cultural resilience. Using a literature review method with a qualitative-descriptive approach, this study explores the integration of the people-centered security concept in the context of Indonesia's demographic transition, which is undergoing a second demographic transition. The findings show that although Indonesia has an adequate regulatory framework, there are still significant gaps in operationalizing the principles of human security, which include freedom from fear and freedom from want. Existing population policies have not fully accommodated the dimensions of economic security, community security, political security, and cultural security, as reflected in the fragmentation of policy approaches and weak cross-sectoral coordination. An integrative human security implementation model through adaptive population governance shows great potential in optimizing the demographic dividend and mitigating the risks of the demographic burden. The implementation of this model contributes significantly to strengthening economic resilience through sustainable economic growth, social resilience through community empowerment, and cultural resilience through the preservation of identity in the era of globalization. The interconnectedness between the three pillars of resilience creates a multiplier effect that strengthens Indonesia's national resilience system in facing future demographic challenges.